PROFESSIONAL FACE-THREAT AND ORAL PARTICIPATION AMONG PHILOLOGY UNDERGRADUATES IN ESP COURSES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Oral participation is a fundamental component of English for Specific Purposes (ESP) education, particularly for philology undergraduates preparing for future academic and professional communication. However, many students experience speaking anxiety due to the fear of negative evaluation and professional face-threat during classroom interaction. This study investigates how professional face-threat influences oral participation among philology undergraduates in ESP courses. The research examines the relationship between teacher evaluative discourse, peer judgment, self-confidence, and students’ willingness to communicate in English. A qualitative research methodology was employed through classroom observation and semi-structured interviews conducted with undergraduate students enrolled in ESP programs. The findings reveal that fear of losing professional image and academic credibility significantly reduces classroom participation and increases communication avoidance. The study further demonstrates that supportive teacher discourse and psychologically safe classroom environments positively influence students’ confidence and oral engagement. The article highlights the importance of emotionally sensitive teaching practices and face-supportive interaction in ESP education.
Keywords: professional face-threat, oral participation, ESP, speaking anxiety, evaluative discourse, philology undergraduates, classroom interaction